Effective Tuberculosis Contact Investigation Using Interferon-Gamma Release Assays. Issue 4 (April 2019) - Bennet, Rutger; Nejat, Sahar; Eriksson, Margareta
Abstract : During 2000 to 2018, 1831 children were screened as part of tuberculosis contact investigation at the Stockholm Northern Clinic. The risk of a child having a positive tuberculin skin test was 33% and positive interferon-gamma release assay 12%. The risk of tuberculosis disease was 6.1% (tuberculin skin test) and 13% (interferon-gamma release assay) in positive-testing children. Abstract : Supplemental Digital Content is available in the text.